The science of making friends : helping socially challenged teens and young adults - Laugeson, Elizabeth A. (Jossey-Bass, 2013)
"The groundbreaking book that puts the focus on teens and young adults with autism. While a number of programs help young children with autism to develop social skills, until now there have been no such approaches for older kids and adults on the spectrum. This book is based on UCLA's acclaimed PEERS program, the only research-based approach in the world to helping adolescents and young adults with autism make and keep friends. This step-by-step guide helps parents, educators, and others to provide "social coaching" to teens and young adults on the spectrum. The book includes concrete rules and steps of social etiquette identified through research. Parents can use the book to assist in improving conversational skills, expanding social opportunities (including dating), identifying strategies for handling peer rejection, and developing and enhancing friendships. Lessons are taught using didactic teaching narratives, followed by key rules and steps. Laugeson and this groundbreaking approach have been profiled in People magazine. DVD videos included demonstrate the book's lessons clearly and show how to present the material to teens and young adults Offers a treasure trove of behavior exercises for practicing each skill, ranging from joining conversations to handling bullying The book features a bonus DVD with video demonstrations of the skills taught and a mobile application that helps teens and young adults use the strategies in real-world situations"--